2001
DOI: 10.1255/ejms.436
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Betidamino Acid-Containing Somatostatin and Gonadotropin-Releasing Hormone Analogs with Electrospray Mass Spectrometry and Tandem Mass Spectrometry

Abstract: We report the electrospray mass spectra and tandem mass (MS/MS) spectra of a series of chemically-stable somatostatin (SRIF) and gonadotropin-releasing hormone (GnRH) analogs which incorporate acylated or alkylated/acylated aminoglycine residues (betidamino acids) into their structure. In the case of SRIF, we compare the betidamino acid-containing analogs with the equivalent peptide without the betide-type linkage. We observe significant differences in the fragmentation patterns of each class of compound. We e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2005
2005

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…17 Tandem mass spectrometry(MS/MS) is becoming the useful method for the identification of rearrangement phenomenon due to its reliability, sensitivity and speed. 18,19 Several studies have reported unusual fragmentation patterns for N-phosphoryl amino acids and peptide derivatives by using ESI-MS/MS. 20,21 In this paper, stepwise fragmentations of N-phosphoryl dipeptide methyl ester using electrospray ionization (ESI) tandem mass spectrometry (MS/MS) were studied.…”
Section: Introductionmentioning
confidence: 99%
“…17 Tandem mass spectrometry(MS/MS) is becoming the useful method for the identification of rearrangement phenomenon due to its reliability, sensitivity and speed. 18,19 Several studies have reported unusual fragmentation patterns for N-phosphoryl amino acids and peptide derivatives by using ESI-MS/MS. 20,21 In this paper, stepwise fragmentations of N-phosphoryl dipeptide methyl ester using electrospray ionization (ESI) tandem mass spectrometry (MS/MS) were studied.…”
Section: Introductionmentioning
confidence: 99%